PROPELLING TOWARDS SUSTAINABLE AGRICULTURE IN INDIA:STAKEHOLDERS’ PERSPECTIVES IN THE STATES OF PUNJAB, HARYANA,AND UTTAR PRADESH (NATIONAL CAPITAL LAW JOURNAL, 2026)
NA
Keywords: Rural Economics; Agriculture in India